Pembelajaran Persamaan Trigonometri Berbantuan Desmos dengan Model Pembelajaran Probem Based Learning dalam Meningkatkan Hasil Belajar Peserta Didik - Ahmad Isroil; Ilyas; Rahmad Heri Prasetyoadi (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
This study aims to improve student learning outcomes at SMA Unggulan BPPT Al Fattah Lamongan through a problem based learning (PBL) learning model assisted by the Desmos application. This study used a classroom action research design which was carried out in three cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. Data collection techniques using tests and non-tests (observation). The data analysis technique used a quantitative descriptive analysis technique. The results showed that in cycle 1: student learning outcomes, including in the cognitive domain, the average student learning outcomes were 77.16 and 75% completeness. In the psychomotor domain, the average learning outcomes of students are 74.79 and the completeness of students is 75%. Affective Rahah, the average student learning outcomes are 79.42 with 71% completeness. In cycle 2: student learning outcomes, including in the cognitive domain, the average student learning outcomes are 80.54 and completeness is 75%. In the psychomotor domain, the average student learning outcomes are 75.21 and the completeness of students is 75%. Affective Rahah, the average student learning outcomes are 79.73 with 75% completeness. In cycle 3: student learning outcomes, including in the cognitive domain, the average student learning outcomes are 82.91 and completeness is 75%. In the psychomotor domain, the average student learning outcomes are 78.12 and student completeness is 75%. Affective Rahah, the average student learning outcomes is 79.42 with 75% completeness. So it can be concluded that the PBL learning model assisted by the Desmos application can improve student learning outcomes on trigonometric equation material